The Use of Online Social Media Platforms by Tanzania Journalists to Produce and Disseminate Development News - Magolanga, Elisha Merick; Michael, Andindilile; Simba, Fatuma (Tanzania Journal of Engineering and Technology, 2023)
Advancement in Information and Communication Technologies (ICT) are revolutionizing Development Journalism (DJ) into an effective strategy for building competitive economies globally. However, many countries in Africa including Tanzania are slow in tapping potentials of ICT for development journalism. Digital penetration in the form of the Internet and social media are changing the way in which journalists are mobilizing and engaging communities in journalism practises, a key strategy for a competitive digitalised economy. This paper was guided by Development Communication Theory and Diffusion of Innovation Theory to explore the use of online social media by journalists in Tanzania to practice development journalism. Combining quantitative and qualitative methods, this paper analyses risks and benefits of online social media platforms in contributing to national development goals. A total of 15 social media journalists and managers from Mwananchi Digital, Ayo TV and Azam TV gave their insights in this paper. Use of online social media platforms for development news is still in its infancy stage, key findings show that out of 270 (100%) studied news items, only 66 (24%) manifested development news practice. Non-development news accounted for 204 (76%) of news items analysed. There were only four (4) (27%) journalists who use social media as a source of information, and platform for disseminating development news in Ayo TV compared to 3 (20%) in Mwananchi Digital and 5 (33%) in Azam TV. Results call upon some intensive national efforts to empower journalists in the use of ICT and mobilize audience in the changing communication patterns. Keywords: Social-media, development journalism, development news, news verification, citizen journalism, and competitive economy